Comparison of FIB-4, APRI and AST/ALT ratio with FibroScan in patients with NAFLD and type 2 diabetes: a single-center study from Bangladesh - Muhammad Shah Alam; Syeda Tanzina Kalam; Monirul Islam Khan; Jabed Ahmed; Rahul Saha; A. B. M. Kamrul-Hasan (Egyptian Liver Journal)
Abstract Background Hepatic fibrosis is a potential marker of the severity and outcome of non-alcoholic fatty liver disease (NAFLD). The objective of our study was to evaluate the diagnostic performance of non-invasive hepatic indices (FIB-4, APRI, and AST/ALT ratio) compared with FibroScan for assessing the stage of fibrosis in individuals with NAFLD and T2DM. Methods This cross-sectional study was conducted including patients with NAFLD and T2DM at Cumilla Diabetic Hospital from January to December 2024. The FIB-4, APRI, and AST/ALT ratio were calculated and their correlation with FibroScan score were evaluated using Spearman’s rank correlation. Receiver operating characteristic (ROC) curve analysis was used to assess the diagnostic performance. Results We included 255 patients (mean age 45 years) with 71% F1 stage, 8.6% F2 stage, 11.8% F3 stage and 8.6% F4 stage fibrosis. A moderate correlation between FibroScan and FIB-4 (r = 0.62, p < 0.05) and a weak correlation with APRI (r = 0.16, p < 0.05) were observed, with no significant correlation to the AST/ALT ratio (r = 0.08, p > 0.05). FIB-4 showed an AUC of 0.73 (95% CI: 0.65–0.81), with a sensitivity of 80.87% and specificity of 56.24% while APRI showed an AUC of 0.76 (95% CI: 0.69–0.84) with a sensitivity of 80.84% and specificity of 63.18%. The AST/ALT ratio had the lowest AUC (0.58), with 44.29% sensitivity and 72.93% specificity. Conclusion FIB-4 was the most reliable non-invasive tool for detecting advanced fibrosis in patients with NAFLD and T2DM.